Evaluation Of Crumb Rubber And Latex Modified Asphalt Binders For Pavement Crack Sealant Purpose - M Poovaneshvaran, Sharvin (Universiti Sains Malaysia, 2018)
Conventional asphalt binder is widely used as the crack sealing material. Crack sealing is one of the most frequent pavement maintenance method. The level of performance during service life has a close relationship with the properties of asphalt binder used in the pavement or as crack sealant material. The rheological weakness of the conventional asphalt binder had sparked the interest of researchers to use polymer modified binder. The aim of this study is to develop crumb rubber and latex modified asphalt binders for crack sealant purpose. Different percentage of crumb rubber and latex were used which are 5 %, 10 %, 15 % for crumb rubber while 5 % and 10 % for latex. This is the most economical method that can be done in order to prolong the life span of pavement. Sealing the crack can prevent infiltration of water. Zycotherm with the content of 0.1 % by weight of binder was used to ensure strong coating bonds between aggregate and asphalt binders. The study was divided into two phases. The goal of first phase is to test and compare the rheological properties of modified binders and unmodified binder. The rheological properties that had been tested are softening point, penetration value, elastic recovery and torsional recovery. These properties were all tested because it influences the performance of the sealant material. In the second phase, bond test and layer-parallel direct shear (LPDS) test were conducted. Bond test was carried out in order to evaluate the tensile strength of sealant material. LPDS was conducted to measure the asphalt binder resistance to shear stress. The results of rheological properties showed that with the increment in crumb rubber and latex content in the asphalt binder, the softening point of the binder increased significantly. This proved that modified binders are less temperature susceptible. While the penetration value decreases with the addition of crumb rubber and latex. This is due to crumb rubber and latex that has the ability to stiffen the binder. Other than that, elastic recovery and torsional recovery showed a positive result with the addition of modifier. The percentage of recovery for both elastic and torsional are relatively good with the presence of crumb rubber and latex. According to bond test results, by incorporating crumb rubber and latex, it is able to increase the tensile strength of the binder. Long term ageing effect were not considered in this study. While the results from LPDS showed that crumb rubber and latex modified binders have a very good resistance to shear stress. This crumb rubber and latex modified asphalt binders would lead to produce the most environmental friendly sealant material by using recyclable material and plant-based material. It is not only environmental friendly, but the performance of modified binder is far more better than conventional binder.